Pengaruh Model Kooperatif Tipe Jigsaw terhadap Hasil Belajar PKn di Sekolah Dasar - Yulinda, Yulinda; Reinita, Reinita; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The recearch is aimed to know about the influence of using of cooperative jigsaw type model toward the result of PKn student in grade V at SDN 10 sapiran Bukittinggi. The research design of the research is quasy exsperimental design. Sample of the research is class VA and VB. The coubting result of research of data that used is t test founded t count > ttable 2, t-test 2,7577 > 2,0128 at α level of 0.05. So that, it can be concluded that there is a significant influence in using cooperative model in jigsaw type toward the result of student’s PKn study in grade V SDN 10 Sapiran Bukittinggi.  Keywords: Cooperative type jigsaw, Learning Outcome, PKn